The effects of minority stressors in the workplace on same-sex relationships: A collective case study of female couples. Issue 2 (3rd April 2019) - Holman, Elizabeth Grace
Abstract: The purpose of this study is to explore the relational effects of minority stress processes experienced at work by female sexual minority employees. Lesbians, in particular, warrant attention in the work environment, as their experiences with homophobia may be exacerbated by sexist overtones. While scholars have linked hostility in the work environment to individual health and employment outcomes for LGBQ employees, less attention has been given to the cross-contextual effects from work to family life. This collective case study examines the experiences of three lesbian employees and their partners in various workplaces using minority stress border theory. Results show that, for these women, there are negative effects on their same-sex relationships; surprisingly though, several women also discussed positive changes in their relationship as a result of experiences with minority stress processes in the workplace. Implications for future research are discussed.